Utilization of long-acting contraceptive methods and associated factors among married women in Farta Woreda, Northwest Ethiopia: a community-based mixed method study - Eden Workneh Aychew; Yibeltal Alemu Bekele; Alemu Degu Ayele; Anteneh Mengist Dessie; Gizachew Worku Dagnew (BMC, 2022)
Plain English summary Long-acting contraceptive methods (LACM) are methods used to prevent pregnancy for a longer period than short-acting methods. LACM are classified in two categories, reversible and non-reversible (permanent). This study use a community-based quantitative cross-sectional study supplemented with qualitative data among married women from March 1 to 31, 2021 in Farta Woreda northwest Ethiopia. The association between variables was analyzed using bivariate and multivariable binary logistic regression. Statistically significant association was declared at a P-value < 0.05. For the qualitative data, a thematic analysis was made manually. The current study found that the magnitude of long-acting contraceptive methods among married women in Farta Woreda was 14.3% 95% CI [11.5-17.6]. Women's husband education, wealth index, previous use LACM, and attitude were significantly associated with long-acting contraceptive utilization. Besides, fear of side effects and partner opposition were the most common barriers of LACM. This study report that utilization of long-acting contraceptives among married women in Farta Woreda was significantly low as compared to the national reproductive health strategy 2020/21 plan. Therefore, establishing strategies and polices to change women's attitudes and increasing husband education will be essential when designing implementation plans to scale up uptake of LACM.